The Effect of Saccos on Socio-Economic Empowerment of Women in Sironko Town Council Sironko District - Muleme Dan (Uganda Christian University, 2024)
This research report was undertaken to examine the effect of SACCOS on socio-economic empowerment of women in Sironko town council, Sironko district. It was guided by three objectives; to analyze the effect of financial management on socio-economic empowerment of women in Sironko town council, to assess the effect of loan portfolio quality on socio-economic empowerment of women in Sironko town council, to determine the effect of savings mobilization on socio-economic empowerment of women in Sironko town council. The researcher used a sample size of 63 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective showed financial management have a significant effect on socio-economic empowerment of women in Sironko town council. Supported by the following responses; 54% of the respondents were positive to the statement that improved financial literacy and management skills enable women to better navigate the financial system, access credit, and make strategic investments; 62% were positive to the statement that women can build savings, invest in income-generating activities, and secure their future economic stability. Results of the second objective revealed that loan portfolio quality has a significant effect on socio-economic empowerment of women in Sironko town council. Supported by the following responses; 56% of the respondents were positive to the statement that women who have access to high-quality loans are more likely to invest in income-generating activities, 80% of the respondents were positive to the statement that women who receive loans with favorable terms and conditions are more likely to expand their businesses. Results of the third objective showed that savings mobilization have a significant effect on socio-economic empowerment of women in Sironko town council. 62% forming the majority of respondents were positive to the statement that savings mobilization programs can contribute to building the confidence and decision, 51% had a positive response to the statement that savings mobilization programs can contribute to building the confidence and decision. The government should offer financial education and training programs tailored for women to improve their understanding of savings, investments, budgeting, and financial planning. Increase women’s access to banking services, credit facilities, and insurance products to help them manage their finances effectively.
This dissertation was conducted by Muleme Dan under the supervision of Mr Komo Richard and it is being forwarded to the department of Social Sciences.